Genetic diversity estimation of Yunnan indigenous goat breeds using microsatellite markers - Guang‐Xin E; Qiong‐Hua Hong; Yong‐Ju Zhao; Yue‐Hui Ma; Ming‐Xing Chu; Lan Zhu; Yong‐Fu Huang (Ecology and Evolution, 2019)
Abstract Background To assess the genetic diversity of seven Yunnan indigenous goat populations (Fengqing hornless goat, Mile red‐bone goat, Longling goat, Ninglang black goat, Black‐bone goat, Yunling black goat, and Zhaotong goat), their population structures were investigated using 20 microsatellite markers. Results The results indicated that the genetic diversity of these goats was rich. The observed heterozygosity ranged from 0.4667 ± 0.0243 to 0.5793 ± 0.0230, and the mean number of alleles ranged from 4.80 ± 1.61 and 4.80 ± 1.64 to 6.20 ± 2.93. The population structure analysis showed that these seven goat populations were separated into two clusters, consistent with the results from phylogenetic networks, pairwise differences, and STRUCTURE analyses. We speculate that this may have been caused by natural geographical isolation, human migration and economic and cultural exchanges. We suggest removing CSRD247 and ILSTS005, two loci identified to be under positive selection in the present study, from the microsatellite evaluation system of goats. Conclusions The present study may provide a scientific basis for the conservation and utilization of Yunnan indigenous goats.